How Ambidextrous Capability Drives Innovation: A Sequential Mediation Model - Hamida Hunein; Budi Syamtoro; Ahmad Farabi (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the influence of ambidextrous organizational capability on innovation performance. It specifically tests the sequential mediation of absorptive capacity and leadership knowledge in this relationship.Methodology: A quantitative approach was employed, using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Data were collected through surveys from 205 knowledge-intensive firms in Indonesia. The analysis assessed both direct effects and sequential mediation pathways.Results: The findings confirm that ambidextrous organizational capability has a strong positive effect on innovative performance. Crucially, absorptive capacity and leadership knowledge sequentially mediate this relationship. The model explains substantial variance in the endogenous variables, confirming the robustness of the proposed framework. Conclusions: The study concludes that ambidextrous capability enhances innovation not only directly but also by first building the organization's absorptive capacity, which in turn develops leadership knowledge, ultimately driving innovative performance. Limitations: The main limitations are the cross-sectional data, which prevents causal inference, and the reliance on perceptual measures, which may be subject to common method bias. The study also does not account for all industry-specific factors.Contributions: Theoretically, this study validates a sequential mediation model in the innovation value chain. Practically, it provides managers with a roadmap for leveraging ambidextrous strategies through knowledge absorption and leadership development to foster this innovation.